Zinc-doped hydroxyl cobalt oxide and preparation method and application thereof
By preparing a zinc-doped cobalt hydroxyoxide catalyst, the problem of low efficiency in the degradation of metronidazole by existing catalysts was solved, achieving efficient degradation of organic pollutants, especially metronidazole, and the catalyst has good reusability.
Patent Information
- Application Number
- CN202511413073.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2025-12-12
AI Technical Summary
Existing catalysts such as cobalt oxide, spinel cobalt ferrite, and single-atom cobalt have limited efficiency in degrading metronidazole (MNZ) when catalytically activating permonosulfate (PMS), and there is a need to improve catalytic activation performance to increase the degradation rate.
By using zinc-doped cobalt hydroxyoxide as a catalyst, and by adjusting the molar ratio of cobalt to zinc and controlling the crystallinity of the material, a catalyst with high oxygen vacancies and large specific surface area was prepared, thereby enhancing the catalytic activation performance.
It significantly improves the degradation rate of organic pollutants, especially the degradation efficiency of metronidazole, and the catalyst can be reused multiple times while maintaining high efficiency.
Smart Images

Figure CN121103430A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of degrading organic pollutants, and particularly relates to zinc-doped cobalt oxyhydroxide as well as a preparation method and application thereof. BACKGROUND
[0002] With the rapid development of the pharmaceutical industry, the continuous accumulation of antibiotic pollutants in the water environment will seriously harm the environment. Among them, metronidazole (MNZ) as a typical nitroimidazole antibiotic is widely used in medical and animal husbandry. Due to its high water solubility and persistence, MNZ widely exists in surface water and even groundwater, and poses a serious threat to the ecological system and human health due to its high biological toxicity and drug resistance gene induction. Therefore, it is very important to study the water treatment technology suitable for removing MNZ and being environmentally friendly and efficient. The traditional method for removing MNZ mainly based on the heterogeneous advanced oxidation technology (PMS-AOPs) of peroxymonosulfate to oxidize and degrade MNZ; however, the degradation rate of MNZ by peroxymonosulfate alone is limited.
[0003] In order to improve the degradation rate of MNZ by PMS, researchers catalyze and activate PMS by adding catalysts to the system, thereby improving the degradation efficiency of MNZ. At present, cobalt oxide (Co3O4), spinel cobalt ferrite (CoFe2O4) and single-atom cobalt (Co-N-C) are mainly used as heterogeneous cobalt-based catalysts to catalyze and activate PMS. Although these catalysts can improve the degradation rate of PMS in degrading MNZ, the catalytic activation performance of PMS still needs to be improved. SUMMARY
[0004] Therefore, the application provides zinc-doped cobalt oxyhydroxide as well as a preparation method and application thereof. The zinc-doped cobalt oxyhydroxide provided by the application has good catalytic activation performance on peroxymonosulfate as a catalyst, and can significantly improve the degradation rate of organic pollutants.
[0005] In order to solve the above technical problems, the application provides zinc-doped cobalt oxyhydroxide, wherein the molar ratio of cobalt elements to zinc elements in the zinc-doped cobalt oxyhydroxide is 0.1-10:1. The zinc-doped cobalt oxyhydroxide contains oxygen vacancies, and the concentration of the oxygen vacancies is 25-85%. The specific surface area of the zinc-doped cobalt oxyhydroxide is 180-280 m 2 / g; the zinc-doped cobalt oxyhydroxide has a pore structure, the pore size is 5-9 nm, and the pore volume is 0.4-0.7 cm 3 / g.
[0006] Preferably, the molar ratio of the cobalt elements to the zinc elements is 0.1:1, 0.2:1, 0.5:1, 1:1, 2:1, 5:1 or 10:1.
[0007] The application further provides a preparation method of the zinc-doped cobalt oxyhydroxide according to the technical scheme. The soluble cobalt salt, the soluble zinc salt and water are first mixed to obtain a composite metal salt solution; The composite metal salt solution and a strong alkali solution are secondly mixed to obtain a gelatinous precipitate; The gelatinous precipitate is dispersed in water and then thirdly mixed with a sodium hypochlorite solution to obtain the zinc-doped cobalt oxyhydroxide.
[0008] Preferably, the soluble cobalt salt comprises cobalt chloride and / or cobalt nitrate; the soluble zinc salt comprises ZnCl2; the molar ratio of cobalt in the soluble cobalt salt to zinc in the soluble zinc salt is 0.1-10:1; The total molar concentration of cobalt and zinc in the composite metal salt solution is 0.038-0.042 mol / L.
[0009] Preferably, the strong alkali solution comprises a sodium hydroxide solution or a potassium hydroxide solution; the molar concentration of the strong alkali solution is 0.8-1.2 mol / L; The volume ratio of the composite metal salt solution to the strong alkali solution is 50:4.8-5.2.
[0010] Preferably, the second mixing comprises the following steps: the strong alkali solution is secondly added dropwise to the composite metal salt solution and then first ultrasonic treatment is performed; the second adding rate is 0.8-1.2 mL / min, and stirring is performed during the second adding process; the first ultrasonic treatment power is 220-260 W, and the first ultrasonic treatment time is 4.8-5.2 min.
[0011] Preferably, the mass concentration of the sodium hypochlorite solution is 3.8-4.2%; the molar ratio of the total amount of cobalt and zinc in the composite metal salt solution to sodium hypochlorite in the sodium hypochlorite solution is 2:4-5.
[0012] Preferably, the third mixing comprises the following steps: the gelatinous precipitate is dispersed in water and then first added dropwise to the sodium hypochlorite solution; The first adding rate is 0.8-1.2 mL / min, and stirring is performed during the first adding process; After the first adding, the following step is further included: second ultrasonic treatment is performed on the system after the first adding; the second ultrasonic treatment power is 220-260 W, and the second ultrasonic treatment time is 18-22 min; After the second ultrasonic treatment, the following step is further included: solid-liquid separation is performed on the system after the second ultrasonic treatment; the solid obtained through the solid-liquid separation is sequentially subjected to water washing, ethanol washing and drying to obtain the zinc-doped cobalt oxyhydroxide.
[0013] The application further provides application of the zinc-doped cobalt oxyhydroxide prepared by the preparation method in degradation of organic pollutants.
[0014] Preferably, the method for degrading organic pollutants comprises a persulfate heterogeneous advanced oxidation method; and the organic pollutants comprise one or more of metronidazole, p-nitrophenol, tetracycline, levofloxacin, methylene blue and sulfamethoxazole.
[0015] The application provides a zinc-doped cobalt oxyhydroxide, wherein the molar ratio of cobalt elements to zinc elements in the zinc-doped cobalt oxyhydroxide is 0.1-10:1; the zinc-doped cobalt oxyhydroxide contains oxygen vacancies, and the concentration of the oxygen vacancies is 25-85%; the specific surface area of the zinc-doped cobalt oxyhydroxide is 180-280 m 2 / g; and the zinc-doped cobalt oxyhydroxide has a pore structure, wherein the pore size is 5-9 nm, and the pore volume is 0.4-0.7 cm 3 / g. The zinc-doped cobalt oxyhydroxide provided by the application takes the cobalt oxyhydroxide as a matrix, and the crystal structure is regulated by doping of zinc elements; with the increase of the doping amount of zinc elements, the crystallinity of the hybrid gradually transitions from high crystallinity to low crystallinity, and finally changes into an amorphous structure; and the change process of the crystallinity can significantly increase the specific surface area of the hybrid, which effectively controls and regulates the exposure degree of active sites, regulates the concentration of oxygen vacancies (O V ) with strong redox properties, and further optimizes the catalytic activity of the zinc-doped cobalt oxyhydroxide. The zinc is doped into the skeleton of the cobalt-based material in the application, defects can be induced by structural distortion, so that the concentration of oxygen vacancies (O V ) with strong redox properties is increased, and the catalytic activity of the zinc-doped cobalt oxyhydroxide is further improved. The zinc-doped cobalt oxyhydroxide provided by the application contains a high concentration of O V , which can enhance the activation performance of the catalyst on persulfate (PMS), because the presence of O V can reduce the adsorption energy of PMS on the surface of the catalyst, promote electron transfer, and also reduce the energy barrier of the O-O bond in PMS to promote the formation of Co(IV)=O. Zn 2+ and Co 3+ have different charges, and the compound must maintain charge balance to maintain no net charge in the structure; therefore, when Zn replaces the local coordination site of Co in the cobalt compound, it is easy to produce O V . The induced O VThe high specific surface area can be provided, thereby improving catalytic activation performance; meanwhile, local charge density can be induced and surface charge state can be mediated, by changing the electronic structure of the local area and surface of the material, the electronic interaction between the catalyst and PMS can be optimized, thereby significantly improving the efficiency of generating reactive oxygen species (ROS), and finally leading to a substantial improvement in the degradation performance of organic pollutants.
[0016] The application further provides a preparation method of the zinc-doped cobalt oxyhydroxide, which comprises the following steps: first mixing a soluble cobalt salt, a soluble zinc salt and water to obtain a composite metal salt solution; second mixing the composite metal salt solution and a strong alkali solution to obtain a gelatinous precipitate; and third mixing the gelatinous precipitate dispersed in water and a sodium hypochlorite solution to obtain the zinc-doped cobalt oxyhydroxide. V The zinc-doped cobalt oxyhydroxide prepared by the simple co-precipitation oxidation method is rich in O V The crystallinity of the zinc-doped cobalt oxyhydroxide can be controlled by adjusting the molar ratio of Co and Zn, and the change process of the crystallinity can significantly increase the specific surface area of the hybrid, which can effectively control and adjust the exposure degree of the active sites, so that the synergistic optimization of the ultra-high specific surface area and the high concentration of O
[0017] The synthesized bimetallic oxyhydroxide (zinc-doped cobalt oxyhydroxide) is applied to a PMS activation system, and the catalytic activation performance is improved, and the degradation rate of organic pollutants is improved. BRIEF DESCRIPTION OF DRAWINGS
[0018] Figure 1 A flowchart for preparing CoZnO-1 is shown in the figure; Figure 2 SEM images of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in the figure, wherein (a) is an SEM image of CoOOH, (b) is an SEM image of ZnO, and (c) is an SEM image of CoZnO-1; Figure 3 TEM test result images of CoZnO-1 prepared in Example 1 and CoOOH prepared in Comparative Example 1 are shown in the figure, wherein (d) is a TEM image of CoOOH, (e) is a TEM image of CoZnO-1, (f) is an HRTEM image of CoZnO-1, (g) is an SAED image of CoOOH, (h) is an SAED image of CoZnO-1, (i)-(m) are EDS-mapping images of CoZnO-1; Figure 4 XRD spectra of the zinc-doped cobalt oxyhydroxide prepared in Examples 1-7, CoOOH prepared in Comparative Example 1 and ZnO prepared in Comparative Example 2 are shown in the figure. Figure 5 EPR spectra of CoZnO-1 prepared in Example 1 and CoOOH prepared in Comparative Example 1; Figure 6 XPS spectra of CoZnO-1 prepared in Example 1 and CoOOH prepared in Comparative Example 1; Figure 7 Infrared spectra of CoZnO-1 prepared in Example 1, CoZnO-0.5 prepared in Example 4, CoZnO-2 prepared in Example 5, CoOOH prepared in Comparative Example 1 and ZnO prepared in Comparative Example 2; Figure 8 Specific surface area and pore size distribution results of CoZnO-1 prepared in Example 1, CoZnO-0.5 prepared in Example 4, CoZnO-2 prepared in Example 5, CoOOH prepared in Comparative Example 1 and ZnO prepared in Comparative Example 2, wherein a is the adsorption-desorption isotherm and b is the pore size distribution graph; Figure 9 Catalyst performance research results, wherein a is the degradation efficiency of MNZ in different catalytic systems, b is the UV-Vis spectrum of CoZnO-1 / PMS degrading MNZ at different sampling times, c is the comparison results of various parameters, d is the influence of Co / Zn molar ratio on the performance of CoZnO-x / PMS system in degrading MNZ, e is the test results of different catalyst addition amounts, f is the test results of different PMS addition amounts, g is the pH value influence experiment results, h is the cycle experiment results of the reuse performance and stability of CoZnO-1; Figure 10 Data graph obtained from degradation experiments of different organic pollutants; Figure 11 Test results of the influence of different anions and HA on the catalytic degradation system; Figure 12 Columnar comparison graph of the degradation efficiency of systems containing SO4 2- , H2PO4 - , NO3 - and HA; Figure 13 Comparison graph of the utilization rate of PMS and the rate constant k obs in the presence of different anions. DETAILED DESCRIPTION
[0019] The present application provides a zinc-doped cobalt oxyhydroxide, wherein the molar ratio of cobalt element to zinc element in the zinc-doped cobalt oxyhydroxide is 0.1-10:1; The zinc-doped cobalt oxyhydroxide contains oxygen vacancies, and the concentration of the oxygen vacancies is 25-85%. The specific surface area of the zinc-doped cobalt oxyhydroxide is 180-280 m 2 / g; the zinc-doped cobalt oxyhydroxide has a pore structure, the pore size is 5-9 nm, and the pore volume is 0.4-0.7 cm 3 / g.
[0020] The molar ratio of cobalt element to zinc element in the zinc-doped cobalt oxyhydroxide provided by the application is 0.1-10:1, and can be specifically 0.1:1, 0.2:1, 0.5:1, 1:1, 2:1, 5:1 or 10:1.
[0021] In the application, the specific surface area of the zinc-doped cobalt oxyhydroxide is 180-280 m 2 / g, and can be specifically 270.01 m 2 / g, 272.99 m 2 / g or 189.14 m 2 / g; the zinc-doped cobalt oxyhydroxide has a pore structure, the pore size of the zinc-doped cobalt oxyhydroxide is 5-9 nm, and can be specifically 5.61 nm, 8.07 nm or 8.28 nm; the pore volume of the zinc-doped cobalt oxyhydroxide is 0.4-0.7 cm 3 / g, and can be specifically 0.46 cm 3 / g, 0.52 cm 3 / g or 0.62 cm 3 / g; the zinc-doped cobalt oxyhydroxide contains oxygen vacancies, and the concentration of the oxygen vacancies is 25-85%, and can be 30-75%. As one specific embodiment of the application, the average particle size of the zinc-doped cobalt oxyhydroxide can be 50-100 nm.
[0022] In the application, the zinc (Zn) element has a lower electronegativity (1.66, while the electronegativity of Co is 1.88), and has a stable divalent state due to its special electronic structure (3d104s2), and the zinc is doped in the cobalt-based material as a dopant, thereby increasing the oxygen vacancy concentration; the application improves the catalytic activation performance under the joint action of the crystallinity structure and the oxygen vacancies.
[0023] The application further provides a preparation method of the zinc-doped cobalt oxyhydroxide in the above technical solution, and the preparation method comprises the following steps: The soluble cobalt salt, the soluble zinc salt and water are first mixed to obtain a composite metal salt solution; The composite metal salt solution and a strong alkali solution are secondly mixed to obtain a colloidal precipitate; The colloidal precipitate is dispersed in water and mixed with a sodium hypochlorite solution to obtain the zinc-doped cobalt oxyhydroxide.
[0024] The soluble cobalt salt, the soluble zinc salt and water are first mixed to obtain a composite metal salt solution. As an embodiment of the present application, the soluble cobalt salt can include cobalt chloride and / or cobalt nitrate, and can specifically be cobalt chloride or cobalt nitrate; the cobalt chloride can be CoCl2·6H2O, and the cobalt nitrate can be Co(NO3)2·6H2O; the soluble zinc salt can include ZnCl2; the molar ratio of cobalt in the soluble cobalt salt to zinc in the soluble zinc salt can be 0.1-10:1, and can specifically be 0.1:1, 0.2:1, 0.5:1, 1:1, 2:1, 5:1 or 10:1; the water can be ultrapure water; and the total molar concentration of cobalt and zinc in the composite metal salt solution can be 0.038-0.042 mol / L, and can specifically be 0.04 mol / L.
[0025] After obtaining the composite metal salt solution, the composite metal salt solution and a strong alkali solution are second mixed to obtain a colloidal precipitate. As an embodiment of the present application, the strong alkali solution can include a sodium hydroxide solution or a potassium hydroxide solution; the molar concentration of the strong alkali solution can be 0.8-1.2 mol / L, and can specifically be 1 mol / L; and the volume ratio of the composite metal salt solution to the strong alkali solution can be 50:4.8-5.2, and can specifically be 50:5.
[0026] As an embodiment of the present application, the second mixing can include the following steps: first ultrasonic treatment after second dropwise addition of the strong alkali solution to the composite metal salt solution; the rate of the second dropwise addition can be 0.8-1.2 mL / min, and can specifically be 1 mL / min; stirring can be accompanied during the second dropwise addition, and the present application does not have special limitations on the stirring as long as it can be uniformly mixed; the power of the first ultrasonic treatment can be 220-260 W, and can specifically be 240 W; and the time of the first ultrasonic treatment can be 4.8-5.2 min, and can specifically be 5 min.
[0027] The reaction occurring during the second mixing of the present application includes formula 1.1 and formula 1.2, and the colloidal precipitate includes cobalt hydroxide and zinc hydroxide: Formula 1.1; Formula 1.2.
[0028] As a specific embodiment of the present application, the second mixing can further comprise: performing solid-liquid separation on the second mixed system to obtain the gelatinous precipitate; the solid-liquid separation can be centrifugation; the speed of the centrifugation can be 8500-9500 rpm, and can be specifically 9000 rpm; the time of the centrifugation can be 0.8-1.2 min, and can be specifically 1 min. In the present application, the gelatinous precipitate is a blue-violet precipitate.
[0029] After obtaining the gelatinous precipitate, the present application disperses the gelatinous precipitate in water and then mixes the gelatinous precipitate with a sodium hypochlorite solution to obtain the zinc-doped cobalt oxyhydroxide. As a specific embodiment of the present application, the mass concentration of the sodium hypochlorite solution can be 3.8-4.2%, and can be specifically 4%; the molar ratio of the total amount of cobalt and zinc in the complexable metal salt solution to the amount of sodium hypochlorite in the sodium hypochlorite solution can be 2:4-5, and can be specifically 2:4.75.
[0030] As a specific embodiment of the present application, the third mixing can comprise the following steps: first adding the gelatinous precipitate dispersed in water to the sodium hypochlorite solution; the rate of the first addition can be 0.8-1.2 mL / min, and can be specifically 1 mL / min; the first addition can be accompanied by stirring, and the present application does not have special limitations on the stirring as long as the stirring can be uniform.
[0031] As a specific embodiment of the present application, the first addition can further comprise: performing second ultrasonic treatment on the system after the first addition; the power of the second ultrasonic treatment can be 220-260 W, and can be specifically 240 W; the time of the second ultrasonic treatment can be 18-22 min, and can be specifically 20 min.
[0032] The reaction of adding sodium hypochlorite to the gelatinous precipitate dispersion liquid of the present application comprises formula 1.3 and formula 1.4: Formula 1.3; Formula 1.4.
[0033] As a specific embodiment of the present application, the second ultrasonic treatment can further comprise: performing solid-liquid separation on the second ultrasonic treatment system, and sequentially performing water washing, ethanol washing and drying on the solid obtained by the solid-liquid separation to obtain the zinc-doped hydroxyl cobalt oxide. As a specific embodiment of the present application, the solid-liquid separation can be centrifugation, and the present application does not have special limitations on the centrifugation as long as the solid-liquid separation can be achieved; the water used for the water washing can be ultrapure water, and the number of times of the water washing can be 2-4 times, which can be specifically 3 times; the number of times of the ethanol washing can be 1-3 times, which can be specifically 2 times; the drying can be vacuum drying, the temperature of the vacuum drying can be 55-65℃, which can be specifically 60℃; the time of the vacuum drying can be 11-13h, which can be specifically 12h; the present application does not have special limitations on the vacuum degree of the vacuum drying as long as it is a vacuum condition. The water washing and the ethanol washing can remove the unreacted chemicals remaining on the surface of the product until the pH value approaches neutral. In the present application, the zinc-doped hydroxyl cobalt oxide is black green.
[0034] The present application also provides an application of the zinc-doped hydroxyl cobalt oxide in the above technical solution or the zinc-doped hydroxyl cobalt oxide prepared by the preparation method in the above technical solution as a catalyst in degrading organic pollutants. As a specific embodiment of the present application, the method for degrading organic pollutants can comprise a peroxymonosulfate heterogeneous advanced oxidation method; the organic pollutants can comprise one or more of metronidazole (MNZ), p-nitrophenol (PNP), tetracycline (TC), levofloxacin (LEV), methylene blue (MB) and sulfamethoxazole (SMX), which can be specifically metronidazole, p-nitrophenol, tetracycline, levofloxacin, methylene blue or sulfamethoxazole.
[0035] As a specific embodiment of the present application, the method for degrading organic pollutants by using zinc-doped cobalt oxyhydroxide as catalyst comprises the following steps: mixing organic pollutants, catalyst and water, and then adding a persulfate solution to degrade the organic pollutants, to obtain a degradation product of the organic pollutants. As a specific embodiment of the present application, the mixing can be carried out under stirring, and the stirring speed is 200-240 rpm, which can be specifically 210 rpm, 220 rpm or 230 rpm; the mass concentration of the organic pollutants in the system after mixing can be 18-22 mg / L, which can be specifically 20 mg / L; the mass of the catalyst to the volume of water in the system after mixing can be 0.05-0.2 g:1 L, which can be specifically 0.05 g:1 L, 0.1 g:1 L, 0.15 g:1 L or 0.2 g:1 L. As a specific embodiment of the present application, the molar concentration of the persulfate in the degradation system can be 1-5 mmol / L, which can be specifically 1 mmol / L, 1.5 mmol / L, 2 mmol / L, 3 mmol / L or 5 mmol / L.
[0036] As a specific embodiment of the present application, the degradation conditions of the zinc-doped cobalt oxyhydroxide as catalyst for degrading organic pollutants can further comprise that the initial pH value of the system can be 3.5-10.5, which can be specifically 3.5, 4, 5, 6.8, 9, 10 or 10.5.
[0037] In the present application, the zinc-doped cobalt oxyhydroxide as catalyst can be repeatedly used in the process of degrading organic pollutants, and the number of times of repeated use is 4 or more, and the degradation rate of the organic pollutants (such as MNZ, PNP, TC, LEV, MB or SMX) is still above 90% after being used for 4 times.
[0038] In order to further illustrate the present application, the technical solutions provided by the present application are described in detail below in combination with examples, but they should not be understood as limiting the scope of protection of the present application.
[0039] Example 1 CoCl2·6H2O (1 mmol) and ZnCl2 (1 mmol) were ultrasonically dispersed in 50 mL of ultrapure water to obtain a purple composite metal salt solution. 5 mmol of NaOH was ultrasonically dispersed (240 W, 5 min) in 5 mL of ultrapure water to obtain a NaOH solution with a molar concentration of 1.0 mol / L. The NaOH solution was slowly dropped into the composite metal salt solution at a rate of 1 mL / min, and stirred while dropping, and then ultrasonically treated for 5 min, and centrifuged at a speed of 9000 rpm for 1 min to obtain a blue-purple gelatinous precipitate (Co(OH)2 and Zn(OH)2).
[0040] The blue-purple gummy precipitate was dispersed in 50 mL of ultrapure water and then added dropwise into a 4% NaCI O (4.75 mmol) solution at a rate of 1 mL / min, stirring while dropping, and then ultrasonicating (240 W, 20 min) for 20 min. The solid was collected after centrifugation, washed with ultrapure water three times and then with ethanol twice, and then ground after drying in a vacuum oven at 60 °C for 12 h to obtain black-green zinc-doped cobalt oxyhydroxide, denoted as CoZnO-1.
[0041] Figure 1 A flowchart for preparing CoZnO-1.
[0042] Example 2 Zinc-doped cobalt oxyhydroxide was prepared according to the method of Example 1, except that the amount of CoCI2-6H2O was 0.18 mmol and the amount of ZnCI2 was 1.82 mmol, and the obtained zinc-doped cobalt oxyhydroxide was denoted as CoZnO-0.1.
[0043] Example 3 Zinc-doped cobalt oxyhydroxide was prepared according to the method of Example 1, except that the amount of CoCI2-6H2O was 0.33 mmol and the amount of ZnCI2 was 1.67 mmol, and the obtained zinc-doped cobalt oxyhydroxide was denoted as CoZnO-0.2.
[0044] Example 4 Zinc-doped cobalt oxyhydroxide was prepared according to the method of Example 1, except that the amount of CoCI2-6H2O was 0.67 mmol and the amount of ZnCI2 was 1.33 mmol, and the obtained zinc-doped cobalt oxyhydroxide was denoted as CoZnO-0.5.
[0045] Example 5 Zinc-doped cobalt oxyhydroxide was prepared according to the method of Example 1, except that the amount of CoCI2-6H2O was 1.33 mmol and the amount of ZnCI2 was 0.67 mmol, and the obtained zinc-doped cobalt oxyhydroxide was denoted as CoZnO-2.
[0046] Example 6 Zinc-doped cobalt oxyhydroxide was prepared according to the method of Example 1, except that the amount of CoCI2-6H2O was 1.67 mmol and the amount of ZnCI2 was 0.33 mmol, and the obtained zinc-doped cobalt oxyhydroxide was denoted as CoZnO-5.
[0047] Example 7 Zinc-doped cobalt oxyhydroxide was prepared according to the method of Example 1, except that the amount of CoCl2·6H2O was 0.1.82), and the amount of ZnCl2 was 0.18 mmol. The obtained zinc-doped cobalt oxyhydroxide was denoted as CoZnO-10.
[0048] Comparative Example 1 CoCl2·6H2O (2 mmol) was ultrasonically dispersed in 50 mL of ultrapure water to obtain a cobalt chloride solution. 5 mmol of NaOH was ultrasonically dispersed in 5 mL of ultrapure water to obtain a NaOH solution with a molar concentration of 1.0 mol / L. The NaOH solution was slowly dripped into the cobalt chloride solution at a rate of 1 mL / min, stirring while dripping, followed by ultrasonic treatment for 5 min, centrifugation at a speed of 9000 rpm for 1 min, to obtain Co(OH)2.
[0049] After Co(OH)2 was dispersed in 50 mL of ultrapure water, it was dripped into a NaClO solution with a mass concentration of 4% (4.75 mmol) at a dripping rate of 1 mL / min, stirring while dripping, and then ultrasonic treatment for 20 min. After centrifugation, the solid was collected, washed with ultrapure water for 3 times, and then washed with ethanol for 2 times. After drying in a vacuum oven at 60°C for 12 h, cobalt oxyhydroxide was obtained by grinding, denoted as CoOOH.
[0050] Comparative Example 2 ZnCl2 (2 mmol) was ultrasonically dispersed in 50 mL of ultrapure water to obtain a zinc chloride solution. 5 mmol of NaOH was ultrasonically dispersed in 5 mL of ultrapure water to obtain a NaOH solution with a molar concentration of 1.0 mol / L. The NaOH solution was slowly dripped into the zinc chloride solution at a rate of 1 mL / min, stirring while dripping, followed by ultrasonic treatment for 5 min, centrifugation at a speed of 9000 rpm for 1 min, to obtain Zn(OH)2.
[0051] After Zn(OH)2 was dispersed in 50 mL of ultrapure water, it was dripped into a NaClO solution with a mass concentration of 4% (4.75 mmol) at a dripping rate of 1 mL / min, stirring while dripping, and then ultrasonic treatment for 20 min. After centrifugation, the solid was collected, washed with ultrapure water for 3 times, and then washed with ethanol for 2 times. After drying in a vacuum oven at 60°C for 12 h, zinc oxide was obtained by grinding, denoted as ZnO.
[0052] The CoZnO-1 prepared in Example 1, the CoOOH prepared in Comparative Example 1, and the ZnO prepared in Comparative Example 2 were detected by scanning electron microscopy (SEM, Tescan Mira4), and SEM images were obtained as follows: Figure 2SEM images of (a) CoOOH, (b) ZnO, and (c) CoZnO-1 are shown.
[0053] CoZnO-1 prepared in Example 1 and CoOOH prepared in Comparative Example 1 were detected by transmission electron microscopy (TEM, FEI Talos F200X), and TEM images were obtained as shown in FIG. 2, wherein (d) is a TEM image of CoOOH, (e) is a TEM image of CoZnO-1, (f) is a HRTEM image of CoZnO-1, (g) is a SAED image of CoOOH, (h) is a SAED image of CoZnO-1, (i)-(m) are EDS-mapping images of CoZnO-1, and the element distribution results obtained are listed in Table 1. Figure 3
[0054] Table 1 Element analysis results of CoZnO-1
[0055] The SEM results show that pure CoOOH presents a stacked nanosheet structure, with a diameter of about 100-150 nm and a thickness of 5-15 nm, and there are many pores and cracks on the surface, indicating that it should have a high specific surface area (BET= 50.6 m2 / g) Figure 2 (a)). ZnO presents a typical nanorod agglomeration structure, with a neat arrangement and a smooth surface, and the nanorods have a diameter of 50-100 nm and a length of 500-1000 nm, without obvious defects or pores (b), and the smooth surface and neat arrangement indicate that it has good crystallinity, which helps to improve the stability and performance of the material. Figure 2 (c) shows that after the addition of Zn, CoZnO-1 presents a near-spherical nanoparticle structure, with a smaller particle size of 50-100 nm, and the surface is rough, indicating that the specific surface area will be further increased, providing more interfaces and contact points. Figure 2 From the TEM, it can be seen that the pure CoOOH particles present a regular hexagonal morphology, corresponding to the SEM images, and there are indeed many pores on the surface (d). While the morphology of CoZnO-1 is irregular, with many stacked sheets (e), further indicating that the addition of Zn leads to a significant decrease in the crystallinity of CoZnO-1, with a highly disordered lattice arrangement. This indicates that the incorporation of Zn may lead to a large number of defects in the structure of CoZnO-1. In the HRTEM image of CoZnO-1, there are fewer clear lattice lines (f).
[0056] Figure 3 Figure 3 Figure 3 In the middle (f), because the material lacks long-range ordered crystal structure, the atomic arrangement is disordered and cannot form regular lattice fringes. However, since ZnO has good crystallinity, the lattice spacing of 0.248 nm is consistent with the (101) crystal plane of ZnO. At the same time, the lattice spacing of 0.231 nm is also found to be consistent with the (012) crystal plane of CoOOH, but the lattice line here is obviously weaker. This indicates that a tight interface contact is formed in the material, confirming the successful synthesis of the CoZnO heterostructure. It can be described that there is a certain arrangement rule and symmetry in the short-range, and there is a local ordered structure similar to a crystal, i.e., short-range order. However, most of the areas in the figure show uniform disordered structure, indicating that the material is almost amorphous. In addition, the SAED image of CoOOH in the middle (g) can be seen to be composed of sharp diffraction spots forming a polycrystalline diffraction ring, and the calibration result is hexagonal CoOOH. However, the SAED image of CoZnO-1 in the middle (h) shows a typical amorphous diffraction halo, which further confirms the authenticity of the amorphous structure of the CoZnO-1 catalyst, which corresponds to the XRD results. As shown in (i)~(m) and Table 1, the EDS mapping further indicates that the O (32.63 wt%), Co (32.91 wt%) and Zn (34.45 wt%) elements are uniformly distributed in the entire CoZnO-1 composite. Figure 3 Figure 3 Figure 3
[0057] The structure and composition of the zinc-doped cobalt hydroxyl oxide prepared in Examples 1~7, the CoOOH prepared in Comparative Example 1 and the ZnO prepared in Comparative Example 2 were analyzed by an X-ray diffractometer (XRD, Bruker D8 Advance), and the test conditions were as follows: the target was a copper target, the scanning range was 10~80º, and the scanning speed was 2 ° / min. The obtained XRD spectrum is shown in Figure 4
[0058] Figure 4 It can be seen that the diffraction peaks of ZnO, CoZnO-0.1 and CoZnO-0.2 are consistent with the standard card (JCPDS No. 79-0207), corresponding to the crystal face of wurtzite ZnO. And with the increase of the cobalt-zinc ratio in zinc-doped hydroxyl cobalt oxide, i.e. the increase of Co content, the diffraction peak intensity decreases significantly, which indicates that the degree of lattice disorder increases and the crystallinity of the sample decreases. Secondly, the diffraction peaks of CoOOH are consistent with the standard card (JCPDS No. 73-0497), corresponding to the crystal face of water cobalt mineral CoOOH, indicating the successful synthesis of CoOOH. With the decrease of the cobalt-zinc ratio, i.e. the increase of Zn content, the diffraction peaks gradually weaken and disappear. When the cobalt-zinc ratio is 1, the diffraction signal intensity of the material CoZnO-1 is the weakest, which is amorphous and has a large number of defects. In addition, with the addition of Zn, the peaks on CoZnO-10 and CoZnO-5 move to low angles, which indicates that due to the addition of Zn, the material produces crystal defects or structural distortion. Low crystallinity (tending to be amorphous) materials usually have more surface defects and active sites, which can reduce the reaction activation energy and thus improve the catalytic reaction rate. Low crystallinity is also conducive to the generation of O V , which can stably adsorb PMS and thus improve the catalytic performance. V
[0059] The paramagnetic resonance spectrometer (EPR, Bruker EMXplus) was used to detect the oxygen defects and free radical and non-free radical capture experiments in the reaction system of CoZnO-1 prepared in Example 1 and CoOOH prepared in Comparative Example 1, and the obtained EPR spectrum is shown in Figure 5 .
[0060] The X-ray photoelectron spectrometer (XPS, Thermo Fischer Escalab 250xi) was used to analyze the composition and state of the surface elements of CoZnO-1 prepared in Example 1 and CoOOH prepared in Comparative Example 1, and the test conditions were Al-kα X-ray; and the obtained XPS spectrum is shown in Figure 6 .
[0061] The Fourier infrared spectrometer (FT-IR, Thermo Fischer NICOLETIS10) was used to study the chemical bonds and identify chemical species of CoZnO-1 prepared in Example 1, CoZnO-0.5 prepared in Example 4, CoZnO-2 prepared in Example 5, CoOOH prepared in Comparative Example 1 and ZnO prepared in Comparative Example 2, and the test conditions were mid-infrared KBr beam splitter, DTGS detector, KBr window, and the scanning range was 4000~525 cm -1 , and the obtained infrared spectrum is shown in Figure 7 .
[0062] From the EPR spectra of CoZnO-1 and CoOOH, it can be seen that both of them observed the signal of O Figure 5 unpaired electrons at g = 2.003, but the signal of O V unpaired electrons on CoZnO-1 is stronger, i.e. has more O V unpaired electrons, which means that CoZnO-1 has more O V .
[0063] From the high-resolution spectra of O 1s of CoZnO-1, it can be seen that the peaks at 534.03, 531.57 and 529.78 eV are attributed to chemisorbed oxygen species Oc, surface adsorbed oxygen species O V on oxygen vacancies and lattice oxygen Co-O bond, respectively. Compared with CoOOH, the content of O V increases in CoZnO-1. The content of O V in CoOOH is 69.55%, while the content of O V in CoZnO-1 increases to 73.84%, which is also in line with the EPR results. Figure 6 From the FTIR spectra of CoZnO-1 and CoOOH, it can be seen that the absorption peaks observed at about 562, 1637, 2975 and 3303 cm -1 correspond to the Co-O 2- , Co-O and -OH bonds present in CoOOH, respectively. Among them, the characteristic peak at 3303 cm -1 is the stretching vibration of the -OH adsorbed on the surface of the material, and the characteristic peak at 2975 cm -1 represents the vibration of the -OH bond near Co. The absorption peak appearing near 1050 cm -1 can be attributed to the Cl-O stretching vibration, which is due to the residual ClO - after the use of NaClO in the synthesis process. The doublet appearing in the interval of 1380~1480 cm -1 is due to the splitting of the anti-symmetry stretching vibration of CO3 2- because of the reduction of symmetry (coordination or adsorption on the surface with metal ions), which is a common phenomenon in materials synthesized under the condition of using NaOH and air environment. After comparing the spectra of samples with different cobalt-zinc ratios, it is found that the intensity of Co-O bond increases with the addition of Zn, which is due to the interaction between Zn atoms and Co atoms, which affects the intensity of Co-O bond. In addition, the intensity of -OH bond at 3303 cm -1 also increases with the addition of Zn, which means that the density of surface hydroxyl increases, which is also conducive to improving the adsorption performance of PMS on the surface of the catalyst to promote the activation of PMS.
[0064] Figure 7
[0065] The specific surface area and pore size distribution of CoZnO-1 prepared in Example 1, CoZnO-0.5 prepared in Example 4, CoZnO-2 prepared in Example 5, CoOOH prepared in Comparative Example 1, and ZnO prepared in Comparative Example 2 were detected using a specific surface area and pore size analyzer (BET, Merck ASAP-3020). The N2 adsorption-desorption isotherms and pore size distribution diagrams are shown below. Figure 8 As shown in the figure, a is the adsorption-desorption isotherm and b is the pore size distribution diagram; the obtained surface area and pore size structure parameters are listed in Table 2.
[0066] Table 2. Specific surface area and pore structure parameters of the catalyst
[0067] Depend on Figure 8 As can be seen from line a, ZnO belongs to the type II isotherm, and at the same time, referring to... Figure 8 The pore size distribution curve of sample b corresponds to that in Table 2, indicating that ZnO is approximately non-porous. The other four samples all exhibit type IV isotherms and H3 hysteresis loops, indicating the presence of mesopores. The mesoporous structure of the catalyst facilitates its contact with contaminants and avoids the mass transfer resistance caused by excessively small pore sizes in micropores, ensuring rapid diffusion of PMS molecules to the active sites within the pores. Corresponding pore size distribution ( Figure 8 In Table 2, the pore sizes of most samples fall between 5 and 15 nm, with CoOOH exhibiting the largest pore size, potentially indicating the presence of macropores, while CoZnO-1 has the smallest pore size. As listed in Table 2, the BET specific surface area of the samples is CoZnO-1 > CoZnO-0.5 > CoZnO-2 > CoOOH > ZnO. Compared to pure CoOOH, the composite material has a larger specific surface area and pore volume, and smaller pore size, indicating the presence of many defect sites in the composite material. This provides more active sites for the PMS activation reaction, which is more conducive to the mass transfer process. The high specific surface area of the catalyst can provide more active sites for pollutants, thereby greatly improving its degradation efficiency. Among them, CoZnO-1 (272.99 nm) has the largest pore size. 2 ( / g) exhibits optimal degradation performance.
[0068] Test case 1.1 Test Methods Method for catalytic degradation: MNZ was used as the target pollutant to evaluate the performance of the catalyst in activating PMS to remove organic pollutants. All batch experiments were conducted at room temperature (25 ± 2 °C). The catalyst was dispersed in a beaker with an aqueous solution of MNZ under stirring at 220 rpm on a shaker, and the timing was started immediately after the addition of a certain amount of PMS solution. The initial MNZ concentration was 20 mg / L, the catalyst material dosage was 0.1 g / L, the PMS addition amount was 2 mmol / L, and the total volume of the solution was 100 mL. During the reaction process, samples were taken from the solution at intervals, filtered through a 0.45 pm polyether sulfone filter, and immediately quantitatively analyzed for the residual MNZ concentration in the solution (the UV maximum absorption wavelength of MNZ is 319 nm) using a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific). In addition, 1 mL of the filtered sample solution was quickly quenched with 1 mL of 100 mmol / L Na2S2O3 solution to stop the reaction. Then, the residual MNZ concentration was also quantitatively analyzed by high-performance liquid chromatography (LC-P100, Shanghai Wufeng Scientific Instrument Co., Ltd., China) with an Eclipse Plus C-18 chromatographic column (4.6 x 150 mm, 5 pm), a mobile phase of a mixture of acetonitrile and water (1:1, v / v), a UV detector wavelength of 319 nm, a sample injection amount of 20 pL, and a flow rate of 1 mL / min.
[0069] The effects of catalyst dosage, PMS dosage, MNZ initial concentration, and solution pH on the reaction system were verified. In the reactive oxygen species (ROS) exploration experiment, methanol (MeOH), tert-butyl alcohol (TBA), chloroform (CF), L-histidine (L-His), and dimethyl sulfoxide (DMSO) were used to scavenge SO4 ·- , ·OH, ·O2⁻, 1 O2, and Co(IV)=O in the reaction system, respectively, to determine the ROS involved. NaCl, NaHCO3, Na2SO4, NaH2PO4, and NaNO3 were used to simulate anions in real water bodies, and HA was used to explore the effect of macromolecular organic matter on the system. In addition, a recycling experiment was also conducted to explore the reusability and stability of the catalyst. After each experiment, the used catalyst was collected by filtration, dried, and then reused without further treatment. The experimental process was the same as the above degradation experiment. In the pH effect experiment, 0.1 M NaOH or 0.1 M HC1 was used to adjust the pH of the solution to 3.5-10.5. It is worth noting that the experiment was conducted three times, and the results are expressed as the average value.
[0070] The utilization of PMS was analyzed on a BioMate 3S UV-Vis spectrophotometer according to the following steps. First, a KI stock solution was prepared by adding 0.166 g KI and 0.04 g NaHCO3 in 100 mL deionized water. Then, 0.1 mL sample solution was mixed with 4.9 mL KI stock solution using a pipette gun, and the absorbance A was measured at 352 nm after oscillation for 5 min. A0 and A were obtained 30 The utilization of PMS was calculated by the formula R PMS = (A0−A 30 ) / A0× 100%.
[0071] The linear relationship between the absorbance A and the concentration C (mg / L) of the pollutants in the solution was measured by a UV-Vis spectrophotometer, as shown in formula (1.5): MNZ: (1.5); The linear relationship between the absorbance A and the concentration C (mg / L) of the pollutants in the solution was measured by a UV-Vis spectrophotometer, as shown in formula (1.5): MB: (1.6); The linear relationship between the absorbance A and the concentration C (mg / L) of the pollutants in the solution was measured by a UV-Vis spectrophotometer, as shown in formula (1.7): TC: (1.7); The linear relationship between the absorbance A and the concentration C (mg / L) of the pollutants in the solution was measured by a UV-Vis spectrophotometer, as shown in formula (1.8): LEV: (1.8); The linear relationship between the peak area S and the concentration C (mg / L) of the pollutants in the solution was measured by high-performance liquid chromatography, as shown in formula (1.9): MNZ: (1.9); The linear relationship between the peak area S and the concentration C (mg / L) of the pollutants in the solution was measured by high-performance liquid chromatography, as shown in formula (1.10): PNP: (1.10); The linear relationship between the peak area S and the concentration C (mg / L) of the pollutants in the solution was measured by high-performance liquid chromatography, as shown in formula (1.11): SMX: (1.11).
[0072] The removal rate of the pollutants was calculated according to formula (1.12): (1.12) wherein C0 and Ct C0and Ctare the pollutant concentrations at initial time and time t, respectively, mg / L.
[0073] MNZ in the degradation process, in line with pseudo-first-order kinetic model, such as formula (1.13): (1.13) Wherein, k obs is the pseudo-first-order apparent rate constant, unit is min -1 .
[0074] k-value (min -1 M -1 ) represents the modified kinetic rate constant of MNZ degradation, by normalizing k obs relative to the catalyst dosage, co-catalyst (PMS) concentration, according to the MNZ concentration scaling calculation, such as formula (1.14): (1.14) Wherein, [Catalyst] is the catalyst dosage, unit is g / L; [PMS] is the co-catalyst concentration, unit is mM; [MNZ] is the concentration of metronidazole, unit is mg / L.
[0075] The removal rate of chemical oxygen demand COD is calculated according to formula (1.15): (1.15); Wherein, COD0and COD t are the COD values at initial time and time t, respectively, unit is mg / L.
[0076] The content of metal element leaching in the material was detected by inductively coupled plasma mass spectrometer (ICP-MS, Thermo Fischer iCAP6300). The Zeta potential of the material at different PH was analyzed by Zeta potential analyzer (Malvern Panalytical ZS90). The electrochemical performance of the material was characterized on CHI660E electrochemical analyzer (Chenhua CHI660E).
[0077] DMPO or TEMP was used to capture ROS (SO·4 - , ·OH, ·O2⁻, 1O2and Co(IV)=O) and analyzed by electron paramagnetic resonance spectroscopy (EPR, Bruker EMXplus). PMSO was used to detect Co(IV) in the system, and PMSO and PMSO2were determined by high performance liquid chromatography (HPLC, LC-P100) with acetonitrile and water (1 / 1, v / v) as mobile phase, a flow rate of 1 mL / min, a column temperature of 25 ℃, an injection volume of 20 μL, and a UV detection wavelength of 230 nm (PMSO) and 216 nm (PMSO2).
[0078] 1.3 Catalyst performance research results MNZ was used as the target pollutant to evaluate the performance of the activated PMS in removing organic pollutants by the catalyst. All batch experiments were carried out at room temperature (25 ± 2 ℃). Different catalysts were dispersed in beakers with MNZ aqueous solution under the agitation of a shaker at 220 rpm, and the timing started immediately after the addition of 2 mM PMS solution. The initial MNZ concentration was 20 mg / L, the catalyst material dosage was 0.1 g / L, the PMS addition amount was 2 mM, and the total volume of the solution was 100 mL. During the reaction process, samples were extracted from the solution at intervals, filtered through a 0.45 μm polyether sulfone filter, and immediately quantitatively analyzed for the residual MNZ concentration in the solution by a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0079] Figure 9 In the figure, a is the degradation efficiency of MNZ in different catalyst systems (the inset is the molecular model of MNZ); in the figure, Only CoZnO-1 means that no PMS is added, at this time the solution includes an initial MNZ concentration of 20 mg / L, and the CoZnO-1 dosage is 0.1 g / L without PMS; Only PMS means that no catalyst is added, at this time the solution includes an initial MNZ concentration of 20 mg / L without catalyst, and the PMS addition amount is 2 mM; CoOOH / PMS, CoOOH+ZnO / PMS and CoZnO-1 / PMS mean that both catalyst and PMS are present, at this time the solution includes an initial MNZ concentration of 20 mg / L, and the catalyst pencil is CoOOH, CoOOH+ZnO (1:1 physical mixture) and CoZnO-1, the catalyst dosage is 0.1 g / L, and the PMS addition amount is 2 mM.
[0080] Figure 9(b) shows the UV-Vis spectra of MNZ degradation by CoZnO-1 / PMS measured at different sampling times (0, 1, 3, 5, 7, 10, 15, 20, 30 min), with the maximum UV absorption wavelength of MNZ being 319 nm; (c) compares various parameters of CoOOH and CoZnO-1; (d) shows the degradation efficiency of MNZ in different CoZnO-x / PMS catalytic systems; (e) shows the effect of catalyst dosage on the degradation of MNZ by CoZnO-1 / PMS; (f) shows the effect of PMS concentration on the degradation of MNZ by CoZnO-1 / PMS; (g) shows the effect of initial pH on the degradation of MNZ by CoZnO-1 / PMS (inset: Zeta potential diagram of CoZnO-1); (h) shows the four-cycle test of MNZ degradation using the CoZnO-1 / PMS system.
[0081] like Figure 9 As shown in Figure a, no significant adsorption effect was observed when CoZnO-1 was present alone, indicating that the material itself does not affect the MNZ removal process; however, the MNZ removal rate was only 12.9% when relying solely on PMS self-decomposition. Comparison of three typical catalytic systems revealed that the MNZ removal rates of the CoOOH / PMS, CoOOH+ZnO (1:1 physical mixture) / PMS, and CoZnO-1 / PMS systems were 71.9%, 44.4%, and 99.9%, respectively. The CoZnO-1 composite catalyst showed significantly better performance than the single CoOOH and its physical mixture systems. This performance improvement may stem from the unique heterogeneous structure of CoZnO-1, whose tight interfacial bonding promotes the formation of defect sites, while its amorphous structure provides abundant active sites for the reaction. Notably, the ZnO / PMS system alone showed almost no degradation effect, further confirming the dominant role of Co species in the catalytic reaction. More importantly, the CoZnO-1 / PMS system can achieve rapid degradation of MNZ, almost completely removing MNZ (99.9%) within just 15 minutes, and the apparent reaction rate constant k is obtained from the pseudo-first-order kinetic fitting. obs The value is 0.364 min. -1 The values are ZnO / PMS (0.004 min). -1 CoOOH / PMS (0.063 min) -1 ) and CoOOH+ZnO / PMS (0.013 min) -1 System k obs The values were 91, 5.8, and 28 times higher. These results indicate that the synthesized CoZnO-1 exhibits the best catalytic performance in activating PMS for MNZ degradation.
[0082] During the degradation process, MNZ follows a pseudo-first-order kinetic model, as shown in equation (1.13): (1.13); Where, k obs This is the pseudo-first-order apparent rate constant, in min. -1 .
[0083] Figure 9 In the figure, c represents a comparison of various parameters. The utilization rate of PMS was analyzed using a UV-Vis spectrophotometer following these steps: First, a KI stock solution was prepared by adding 0.166 g KI and 0.04 g NaHCO3 to 100 mL of deionized water. Then, the solution at time 0 and after degradation for 30 min was filtered through a membrane. 0.1 mL of the sample solution was pipetted and mixed with 4.9 mL of the KI stock solution, then shaken for 5 min. The absorbance A was measured at 352 nm to obtain A0 and A2. 30 The utilization rate of PMS is obtained through calculation, and the formula is R. PMS = (A0− A 30 ) / A0× 100%.
[0084] k-value (min) -1 M -1 ) represents the corrected kinetic rate constant for MNZ degradation, expressed as k obs The concentration of catalyst is normalized relative to the catalyst dosage and the concentration of co-catalyst (PMS), and the calculation is scaled according to the concentration of MNZ, as shown in Equation (1.14).
[0085] To evaluate the utilization efficiency of PMS by various catalysts, the consumption of PMS was meticulously quantified. For example... Figure 9 As shown in Figure c, the PMS utilization rate of the CoZnO-1 catalyst was 92.7% within 30 min of reaction. This utilization rate is significantly higher than that of CoOOH (18.8%). Furthermore, the CoZnO-1 / PMS system exhibits a higher total organic carbon (TOC) removal rate. This system can achieve a high MNZ mineralization rate of 45.9% within 30 min, higher than the 15.9% of the CoOOH / PMS system. Notably, the kinetic rate constant k-value for MNZ removal modification was observed to reach 36.4 min⁻¹ M⁻¹ in this system, significantly higher than the 6.3 min⁻¹ M⁻¹ of the CoOOH / PMS system. Figure 9 (c). This pollutant degradation efficiency stems from the material's more efficient activation of PMS, further confirming the superior performance of the CoZnO-1 / PMS system in advanced oxidation technologies.
[0086] Figure 9The effect of Co / Zn molar ratio on the performance of MNZ degradation by CoZnO-x / PMS system is shown in FIG. 6D. The experimental data show that with the decrease of Co / Zn molar ratio (x), the activation performance of the catalyst presents a volcano-type curve change. When x = 1, it reaches the peak value, at this time, MNZ is nearly completely degraded (degradation efficiency 99.9%) within 15 min. It is worth noting that this component-activity volcano-type relationship is highly consistent with the change trend of material crystallinity in XRD characterization, confirming that the formation of low crystallinity and amorphous phase helps to expose active sites, thereby improving the catalytic performance. Based on the above rules, CoZnO-1 is preferred for subsequent research due to its optimal PMS activation ability. However, overall, CoZnO-10, CoZnO-5, CoZnO-2, CoZnO-1, CoZnO-0.5, CoZnO-0.2 and CoZnO-0.1 can all effectively activate PMS to degrade MNZ. The removal rates of MNZ by PMS activated by the above 7 kinds of catalysts are 82.1%, 99.9%, 99.9%, 99.9%, 99.9%, 99.9%, and 99.6%, respectively, at 30 min of degradation.
[0087] Figure 9 The test results of different catalyst addition amounts are shown in FIG. 6E. The experimental method is as follows: MNZ is used as the target pollutant, and all batch experiments are carried out at room temperature (25 ± 2 ℃). Under the stirring of a shaking table at 220 rpm, the catalyst CoZnO-1 and the MNZ aqueous solution are dispersed in a beaker, and 2 mM PMS solution is added immediately after timing starts. The initial MNZ concentration is 20 mg / L, the catalyst CoZnO-1 dosage is 0 (only PMS), 0.05, 0.1, 0.15 and 0.20 g / L, the PMS addition amount is 2 mM, and the total volume of the solution is 100 mL. During the reaction process, samples are extracted from the solution at intervals, filtered through a 0.45 µm polyether sulfone filter, and immediately quantitatively analyzed for the residual MNZ concentration in the solution by a UV-vis spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0088] From the above results, it can be seen that the CoZnO-1 catalyst has the best performance in activating PMS to degrade MNZ. The degradation rate of MNZ by PMS activated by CoZnO-1 is 99.9% within 15 min. The CoZnO-1 catalyst is used for the following experiments. Figure 9It can be found that the MNZ degradation efficiency relying on PMS self-decomposition only is less than 13% without adding catalyst. Subsequently, with the increase of CoZnO-1 dosage from 0.05 g / L to 0.15 g / L, the removal rate of MNZ after 15 min of reaction is improved, which is attributed to the increase of catalyst providing more active sites for catalytic degradation reaction and promoting the activation efficiency of PMS. It is worth noting that when the catalyst dosage is 0.05 g / L, 0.1 g / L and 0.15 g / L, 99.9% of MNZ can still be removed after 20 min of reaction, which highlights the excellent catalytic performance of CoZnO-1. However, when the catalyst dosage increases to 0.2 g / L, the MNZ degradation efficiency slightly decreases to 97.4% and the reaction rate slows down, which is due to the quenching effect of high concentration of free radicals caused by excessive catalyst, which in turn leads to a slight decrease in catalytic degradation efficiency. Moreover, the increase of catalyst dosage also faces the risk of metal ion leaching and the increase of treatment cost.
[0089] Figure 9 The test results of different PMS addition amounts are shown in Table f. The experimental method is as follows: MNZ is used as the target pollutant, and all batch experiments are carried out at room temperature (25 ± 2 ℃). Under the stirring of a shaker at 220 rpm, the catalyst CoZnO-1 and MNZ aqueous solution are dispersed in a beaker, and 2 mM PMS solution is added immediately after timing. The initial MNZ concentration is 20 mg / L, the catalyst CoZnO-1 dosage is 0.1 g / L, and the PMS addition amount is 0 (only CoZnO-1), 1, 1.5, 2, 3 and 5 mM, and the total volume of the solution is 100 mL. During the reaction process, samples are taken from the solution at intervals, filtered through a 0.45 µm polyether sulfone filter, and immediately quantitatively analyzed for the residual MNZ concentration in the solution using a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0090] From Table f Figure 9 It can be found from Table f that when the PMS concentration increases from 1 mM to 2 mM, the MNZ degradation efficiency increases significantly from 64.0% to 99.9%, the MNZ degradation efficiency is 95.0% at 1.5 mM, and the MNZ degradation efficiency is 99.9% at 3 mM and 5 mM. The reaction rate constants at 1, 1.5, 2, 3 and 5 mM are 0.083, 0.147, 0.364, 0.312 and 0.185 min -1However, when the PMS concentration increased to 3 mM and 5 mM, the reaction rate showed a downward trend. This is due to two synergistic factors: on the one hand, the catalytic active site tends to be saturated under the overload of PMS, leading to the accumulation of unactivated PMS on the catalyst surface; on the other hand, the excess PMS has a free radical quenching reaction with ROS, which weakens the effective free radical concentration.
[0091] From the above test results, it can be known that the cobalt-zinc ratio of 1:1 can produce the most effective degradation performance, and the degradation conditions are to set the concentrations of CoZnO-1 and PMS as 0.1 g / L and 2.0 mM respectively. -1 At the same time, CoZnO-10, CoZnO-5, CoZnO-2, CoZnO-1, CoZnO-0.5, CoZnO-0.2 and CoZnO-0.1 can all effectively activate PMS to degrade MNZ. At the degradation time of 30 min, the removal rates of MNZ by PMS activated by the above 7 kinds of catalysts are 81.7%, 99.9%, 99.9%, 99.9%, 99.9%, 99.9%, and 99.1% respectively. CoZnO-1 can effectively degrade MNZ when the concentration is in the range of 0.05~0.2 g / L and the PMS concentration is in the range of 1.0~3.0 mM. -1
[0092] Figure 9 g is the pH value influence experiment result graph; wherein 0.1 M NaOH or 0.1 M HCl is used to adjust the pH of the solution to 3.5~10.5; the experimental method: MNZ is used as the target pollutant, all batch experiments are carried out at room temperature (25 ± 2 ℃), under the stirring of a shaking table at 220 rpm, the catalyst CoZnO-1 and MNZ aqueous solution are dispersed in a beaker, 0.1 M NaOH or 0.1 M HCl is used to adjust the pH of the solution to 3.5~10.5, 2 mM PMS solution is added immediately after timing, the initial MNZ concentration is 20 mg / L, the catalyst CoZnO-1 dosage is 0.1 g / L, the PMS addition amount is 2 mM, and the total volume of the solution is 100 mL. During the reaction process, samples are extracted from the solution at intervals, filtered through a 0.45 µm polyether sulfone filter membrane, and immediately quantitatively analyzed for the residual MNZ concentration in the solution by a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0093] Figure 9 The results of the medium g show that when the initial solution pH is not adjusted, i.e., [pH]0= 6.8, the catalytic activity reaches a peak, at which MNZ is close to complete degradation (degradation efficiency 99.9%) within 15 min. It is worth noting that the CoZnO-1 catalyst has excellent PMS activation ability in a wide pH value range ([pH]0= 4 ~ 10.5), and the degradation efficiency of MNZ remains above 99%. Only when the solution pH is 3.5, the degradation efficiency is slightly reduced (83.1%), but still above 80%, indicating that the catalyst has good catalytic efficiency and outstanding pH adaptability. The experimental data show that with the increase of pH value, the overall performance of the catalyst presents a volcano-type curve change; specifically, under the conditions of pH values of 3.5, 4.0, 5.0, 6.8, 9.0, 10.0, 10.5, the removal rates of MNZ are 83.1%, 99.3%, 99.9%, 99.9%, 99.9%, 99.9%, 99.8%, respectively, and the reaction rate constants are 0.088, 0.146, 0.303, 0.364, 0.264, 0.250, 0.145 min -1 , respectively; when [pH]0< 6.8, the reaction rates of [pH]0= 3.5, 4 and 5 present an ascending order; when [pH]0> 6.8, the reaction rates of [pH]0= 9, 10 and 10.5 present a descending order; when [pH]0= 6.8, the CoZnO-1 reaction rate is the fastest, indicating that this time is most conducive to the degradation of MNZ. The Zeta potential of CoZnO-1 is detected, and the pH pzc of CoZnO-1 is calculated as 6.31; it is shown that when [pH]0< 6.31, the catalyst surface is positively charged; when [pH]0> 6.31, the catalyst surface is negatively charged.
[0094] The acidic conditions ([pH]0= 3.5 and 4) slightly inhibit the degradation of MNZ, which is attributed to the following four reasons: (1) in the acidic medium, a large amount of H + will combine with PMS, inhibiting the interaction between PMS and the surface of CoZnO-1; (2) H + can also make PMS into more stable H2SO5, making its activation more challenging; (3) since pKa (MNZ) = 2.62 < [pH]0 and pKa (PMS) = 9.4 > [pH]0 at this time, the surface of MNZ is negatively charged, but PMS and the catalyst surface are positively charged, the stronger the acidity in the solution, the stronger the electrostatic repulsion between PMS and CoZnO-1, which will hinder the catalytic process and is not conducive to the activation of PMS; (4) excessive H +may react with radicals, leading to the reduced efficiency of MNZ degradation. The alkaline condition ([pH]0= 10.5) also has an impact on the degradation of MNZ, attributed to the following four reasons: (1) when the pH value exceeds 9.4, the less oxidative SO5 2- is substituted for HSO5 - as the dominant form; (2) the negative charge on the surface of CoZnO-1 increases with the increase of pH value, and the electrostatic repulsion between the catalyst and PMS / MNZ is enhanced, which may hinder the adsorption of PMS and the degradation of MNZ; (3) the strong alkaline environment may lead to the deprotonation of the hydroxyl groups on the surface of the catalyst, thus reducing the potential active sites and inhibiting the activation process of the catalyst; (4) under alkaline conditions, PMS will undergo self-decomposition, reducing the overall reaction rate, as shown in Equation 1.16: 1.16.
[0095] Figure 9 Figure h is a graph of the results of the recycling experiments for the reusability and stability study of CoZnO-1. After each experiment, the used catalyst was collected by filtration, dried, and then reused without any further treatment. The experimental process was the same as the above degradation experiment. Experimental method: MNZ was used as the target pollutant, and all batch experiments were carried out at room temperature (25 ± 2 °C). The catalyst CoZnO-1 obtained after different cycles was dispersed in a beaker with MNZ aqueous solution under the stirring of a shaker at 220 rpm. The reaction was started immediately after the addition of 2 mM PMS solution, and the initial MNZ concentration was 20 mg / L. The dosage of catalyst CoZnO-1 was 0.1 g / L, and the amount of PMS added was 2 mM. The total volume of the solution was 100 mL. During the reaction process, samples were taken from the solution at regular intervals, filtered through a 0.45 µm polyether sulfone filter, and immediately analyzed quantitatively for the residual MNZ concentration using a UV-vis spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0096] Figure 10 Figure h shows that the degradation efficiency of MNZ in the four consecutive cycles was 99.9%, 99.9%, 95.2%, and 91.1%, respectively, and still maintained a removal rate of more than 90% after the fourth cycle, indicating excellent stability of the system. This stability is attributed to the amorphous structure of the catalyst, which effectively inhibits the structural collapse of the active sites. At the same time, the amphoteric nature of the Zn component dynamically adjusts the pH value of the solution during the reaction, maintaining a neutral microenvironment through the neutralization reaction, thereby delaying the passivation of the catalyst surface.
[0097] Figure 10are data graphs obtained from degradation experiments with different organic pollutants. Experimental method: MNZ, PNP, TC, LEV and MB were used as target pollutants to evaluate the performance of the catalyst CoZnO-1 activated PMS for the removal of organic pollutants. All batch experiments were carried out at room temperature (25 ± 2 °C). The catalyst CoZnO-1 and the aqueous solution of pollutants were dispersed in a beaker under stirring at 220 rpm. The reaction was started immediately after adding a certain amount of PMS solution. If not specified, the initial pollutant concentration was 20 mg / L, the catalyst CoZnO-1 dosage was 0.1 g / L, the PMS addition was 2 mM, and the total volume of the solution was 100 mL. During the reaction process, samples were taken from the solution at regular intervals, filtered through a 0.45 pm polyethersulfone filter, and immediately analyzed quantitatively for the concentration of residual MNZ, TC, LEV and MB using a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific). In addition, 1 mL of the filtered sample solution was quickly quenched with 1 mL of 100 mM Na2S203 solution to stop the reaction. Then, the residual PNP and SMX concentrations were quantitatively analyzed by high-performance liquid chromatography (LC-P100, Shanghai Wo Feng Scientific Instrument Co., Ltd., China).
[0098] The UV maximum absorption wavelengths of MNZ, tetracycline (TC), levofloxacin (LEV), and methylene blue (MB) were 319, 357, 287, and 665 nm, respectively. The concentrations of p-nitrophenol (PNP) and sulfamethoxazole (SMX) were determined by high-performance liquid chromatography (LC-P100, Shanghai Wo Feng Scientific Instrument Co., Ltd., China) using an Eclipse Plus C-18 chromatographic column (4.6 × 150 mm, 5 pm). The SMX mobile phase was a mixture of acetonitrile and water (1 : 1, v / v), the UV detector wavelength was 319 nm and 266 nm, the PNP mobile phase was a mixture of methanol and water (1 : 1, v / v), the UV detector wavelength was 318 nm, the injection volume was 20 pL, and the flow rate was 1 mL / min.
[0099] Figure 11 It is shown that in the CoZnO-1 / PMS system, the degradation efficiencies of PNP, TC, LEV, MB and SMX within 30 min reached 92.8%, 99.9%, 99.9%, 99.9% and 97.4%, respectively, all showing excellent degradation effects. This high-efficiency and universal degradation performance is due to the high density of O V First, O VPMS activation; secondly, the amorphous structure endows greater specific surface area and active site exposure. In addition, organic pollutants with electron-donating groups (such as the phenolic hydroxyl of TC and the conjugated system of MB) are usually easier to be degraded than those with electron-withdrawing groups. Therefore, PNP containing electron-withdrawing nitro group will reduce the electron density of the molecule, resulting in a slightly slower degradation rate, but the degradation efficiency is still as high as 92.8%. In summary, the amorphous CoZnO-1 rich in O V has great application potential in the degradation of various organic pollutants.
[0100] Figure 12 NaCl, NaHCO3, Na2SO4, NaH2PO4, and NaNO3 were added to simulate anions in real water bodies, and HA was used to test the effect of macromolecular organic matter on the system. Experimental method: MNZ was used as the target pollutant, and all batch experiments were conducted at room temperature (25 ± 2 ℃). Under the stirring of a shaking table at 220 rpm, the catalyst CoZnO-1 was dispersed in a beaker with MNZ aqueous solution, 1 mM of NaCl, NaHCO3, 5 mM of Na2SO4, NaH2PO4, NaNO3, and 5 mg / L of HA were added, and then 2 mM of PMS solution was added immediately to start timing. The initial MNZ concentration was 20 mg / L, the catalyst CoZnO-1 dosage was 0.1 g / L, the PMS addition amount was 2 mM, and the total volume of the solution was 100 mL. During the reaction process, samples were taken from the solution at intervals, filtered through a 0.45 µm polyether sulfone filter, and immediately quantitatively analyzed for the residual MNZ concentration in the solution using a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0101] Figure 13 SO4 2- , H2PO4 - , and NO3 -Bar chart of degradation efficiency of systems with HA. Experimental method: MNZ was used as the target pollutant, and all batch experiments were conducted at room temperature (25 ± 2 °C). The catalyst CoZnO-1 was dispersed in a beaker with MNZ aqueous solution under the agitation of a shaker at 220 rpm, 0, 5, 10, 20 mM of Na2SO4, NaH2PO4, NaNO3 and 0, 5, 10, 20 mg / L of HA were added, respectively, and then 2 mM PMS solution was added immediately to start timing. The initial MNZ concentration was 20 mg / L, the catalyst CoZnO-1 dosage was 0.1 g / L, the PMS dosage was 2 mM, and the total volume of the solution was 100 mL. During the reaction process, samples were extracted from the solution at intervals, filtered through a 0.45 pm polyether sulfone filter, and immediately analyzed for the residual MNZ concentration using a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0102] Figure 11 Comparison chart of PMS utilization rate and rate constant k obs for different anions, experimental method: MNZ was used as the target pollutant, and all batch experiments were conducted at room temperature (25 ± 2 °C). The catalyst CoZnO-1 was dispersed in a beaker with MNZ aqueous solution under the agitation of a shaker at 220 rpm, 0, 1 mM of NaCl, NaHCO3, 5 mM of Na2SO4, NaH2PO4, NaNO3 were added, respectively, and then 2 mM PMS solution was added immediately to start timing. The initial MNZ concentration was 20 mg / L, the catalyst CoZnO-1 dosage was 0.1 g / L, the PMS dosage was 2 mM, and the total volume of the solution was 100 mL, [pH]0= 6.8. During the reaction process, samples were extracted from the solution at intervals, filtered through a 0.45 pm polyether sulfone filter, and immediately analyzed for the residual MNZ concentration using a UV-visible spectrophotometer (UV-vis: BioMate 3S, Thermo Fisher Scientific).
[0103] During the degradation of MNZ, the pseudo-first-order kinetic model was followed, as shown in equation (1.13); the PMS utilization rate was analyzed on a UV-visible spectrophotometer according to the following steps. First, 0.166 g of KI and 0.04 g of NaHCO3 were added to 100 mL of deionized water to prepare a KI stock solution. Then, 0.1 mL of sample solution was taken from the 0-time and 30-min post-degradation solution filter membrane, mixed with 4.9 mL of KI stock solution, and then shaken for 5 min. The absorbance A was measured at 352 nm to obtain A0and A 30The utilization rate of PMS is obtained through calculation, and the formula is R. PMS = (A0− A 30 ) / A0× 100%.
[0104] The degradation efficiency of MNZ at different concentrations of anions and HA is shown in Table 3.
[0105] Table 3 Comparison of decomposition efficiency with different anion and HA concentrations
[0106] Depend on Figure 12 and Figure 13 As can be seen from the test results in Table 3, SO4 2- NO3 - H2PO4 - Furthermore, the fact that HA had almost no effect on the removal of MNZ confirms the non-radical-dominated nature of the CoZnO-1 / PMS system. It is noteworthy that only HCO3-... - and Cl - The addition of [a specific substance] had a significant negative impact on the degradation of MNZ. When the concentration increased to 2 mM, the degradation efficiency decreased by 85.9% and 84.9%, respectively. The results indicate that the entire system has a significant negative impact on the removal of HCO3-. - and Cl - It has strong anti-interference ability against other interference factors besides itself.
[0107] Depend on The test results show that the PMS utilization rate measured under different anions is related to k. obs They exhibit the same trend of change. This means that HCO3... - With Cl - The inhibitory effect on the performance of the reaction system stems from the decrease in the catalytic activity of CoZnO-1; this indicates that HCO3... - With Cl - It can be adsorbed onto the hydroxyl sites on the catalyst surface through ligand exchange. This process competes with the adsorption of PMS at the hydroxyl sites, thereby inhibiting the catalytic performance.
[0108] This invention employs a simple co-precipitation oxidation method to prepare a high-concentration O2 that can be synthesized on a large scale. V A structure-controllable bimetallic hydroxyl oxide, CoZnO-x, can efficiently degrade MNZ via activated PMS. Experimental results show that structural tuning can significantly improve the specific surface area and active site exposure of the material, allowing the lowest crystallinity CoZnO-1 to exhibit the best catalytic performance. Under the conditions of 2 mM PMS and 0.1 g / L CoZnO-1, 20 mg / L of MNZ can be completely degraded within 15 min. obsup to 0.364 min -1 Meanwhile, the PMS utilization rate reached up to 92.7%, and the catalyst exhibited excellent performance in a wide pH range of 4-10.5. The MNZ degradation rate was still over 90% after four cycles, which was attributed to the disorder atomic arrangement of amorphous structure effectively inhibiting the collapse of active sites. In particular, the system had strong anti-interference ability to other interfering ions except HCO3 - and Cl - The HCO3 - and Cl - inhibited the performance of CoZnO-1 by competing for the surface hydroxyl sites, rather than the traditional free radical consumption path. The present application gradually decomposed MNZ into low molecular weight intermediates through hydroxylation, carboxylation, ring opening and chain cleavage, and finally mineralized into CO2, H2O and NO3 - .
[0109] Although the above embodiments have made a detailed description of the present application, it is only a part of the embodiments of the present application, not all the embodiments, and other embodiments can be obtained according to the present embodiments without creativity, which belong to the protection scope of the present application.
Claims
1. A zinc-doped cobalt hydroxyoxide, characterized in that, The molar ratio of cobalt to zinc in the zinc-doped cobalt hydroxyoxide is 0.1 to 10:
1. The zinc-doped cobalt hydroxyoxide contains oxygen vacancies, and the concentration of the oxygen vacancies is 25-85%. The specific surface area of the zinc-doped cobalt hydroxyoxide is 180~280 m². 2 / g; the zinc-doped cobalt hydroxyoxide has a porous structure with a pore size of 5~9nm and a pore volume of 0.4~0.7cm³. 3 / g.
2. The zinc-doped cobalt hydroxyoxide according to claim 1, characterized in that, The molar ratio of cobalt to zinc is 0.1:1, 0.2:1, 0.5:1, 1:1, 2:1, 5:1 or 10:
1.
3. The method for preparing zinc-doped cobalt hydroxyoxide according to claim 1 or 2, characterized in that, Includes the following steps: A soluble cobalt salt, a soluble zinc salt, and water are first mixed to obtain a composite metal salt solution; The composite metal salt solution and the strong alkali solution were mixed for the second time to obtain a colloidal precipitate; The colloidal precipitate was dispersed in water and then mixed with sodium hypochlorite solution to obtain the zinc-doped cobalt hydroxyoxide.
4. The preparation method according to claim 3, characterized in that, The soluble cobalt salt includes cobalt chloride and / or cobalt nitrate; the soluble zinc salt includes ZnCl2; the molar ratio of cobalt in the soluble cobalt salt to zinc in the soluble zinc salt is 0.1~10:1; The total molar concentration of cobalt and zinc in the composite metal salt solution is 0.038~0.042 mol / L.
5. The preparation method according to claim 3, characterized in that, The strong alkali solution includes sodium hydroxide solution or potassium hydroxide solution; the molar concentration of the strong alkali solution is 0.8~1.2 mol / L; The volume ratio of the composite metal salt solution to the strong alkali solution is 50:4.8~5.
2.
6. The preparation method according to claim 3 or 5, characterized in that, The second mixing includes the following steps: adding a strong alkali solution dropwise to the composite metal salt solution and then sonicating for the first time; the second dropwise addition rate is 0.8~1.2 mL / min, and stirring is carried out during the second dropwise addition; the power of the first sonication is 220~260W, and the duration of the first sonication is 4.8~5.2 min.
7. The preparation method according to claim 3, characterized in that, The mass concentration of the sodium hypochlorite solution is 3.8-4.2%; the total molar ratio of cobalt and zinc in the composite metal salt solution to the molar ratio of sodium hypochlorite in the sodium hypochlorite solution is 2:4-5.
8. The preparation method according to claim 3 or 7, characterized in that, The third mixing includes the following steps: dispersing the colloidal precipitate in water and then adding the first drop to the sodium hypochlorite solution; The first dropping rate is 0.8~1.2 mL / min, and stirring is carried out during the first dropping process; The process after the first addition also includes: subjecting the system after the first addition to a second ultrasound, wherein the power of the second ultrasound is 220~260W and the duration of the second ultrasound is 18~22min; The second ultrasound process further includes: performing solid-liquid separation on the system after the second ultrasound, and sequentially washing the solid obtained from the solid-liquid separation with water, washing with ethanol, and drying to obtain the zinc-doped cobalt hydroxyoxide.
9. The application of the zinc-doped cobalt hydroxyoxide according to claim 1 or 2, or the zinc-doped cobalt hydroxyoxide prepared by any one of claims 3 to 8, as a catalyst in the degradation of organic pollutants.
10. The application according to claim 9, characterized in that, The method for degrading organic pollutants includes a persulfate heterogeneous advanced oxidation method; the organic pollutants include one or more of metronidazole, p-nitrophenol, tetracycline, levofloxacin, methylene blue, and sulfamethoxazole.